Digital human resource development: where are we? Where should we go and how do we go there?. Issue 1 (1st January 2022) - Thite, Mohan
ABSTRACT: The purpose of this paper is to trace the evolution of HR-Technology interface leading up to the incorporation of the digital world in Human Resource Development's design thinking, strategizing and execution. Drawing from related empirical studies, the paper critically analyzes Digital HR in terms of where it is now (degree of alignment between external demands and internal capabilities), where it should be (future-focused HR technology strategy), and how it can reach there (implementation road map). The paper presents a comprehensive framework that encompasses external demands, internal capabilities and key recommendations for a fit-for-purpose, future-focused Digital HR Strategy. In the process, the paper adopts a holistic perspective of virtual HRD (VHRD) and draws implications for technology-led developments in the HRD field.